1974
DOI: 10.1104/pp.53.3.352
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome Stability in Vitro

Abstract: Photoreversible phytochrome disappears from etiolated tissue upon actinic irradiation. Such disappearance, of possible physiological importance, involves several processes, at least one of which is accelerated by metals in vivo. Purified phytochrome from oat (Avena sativa L. cv. Garry) coleoptiles is greatly stabilized in vitro by scrupulous removal of metal impurities via chelating agents. Such stabilized phytochrome decays rapidly upon the addition of about 10 AM Hg, Cd&', Cu2', and Zn2', all of which probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
3

Year Published

1975
1975
1991
1991

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
2
9
3
Order By: Relevance
“…The pH of the phytochrome at the taneously preclude correcting the present reversion results for ,es was not adjusted prior to the determination of the loss of phytochrome. Lisansky and Galston (10), on the other netics, since it has been shown that the kinetic param-hand, report that miagnesium and calcium have no effect on tvary over a pH range of 6.2 to 8.2 (16). All manipu-"dark destruction"; they utilized the cations at concentrations r to phototransformation were carried out at 5 C lower than used in the present studies.…”
Section: W F Thompson (Personal Communication) Noted That Caci2mentioning
confidence: 83%
See 1 more Smart Citation
“…The pH of the phytochrome at the taneously preclude correcting the present reversion results for ,es was not adjusted prior to the determination of the loss of phytochrome. Lisansky and Galston (10), on the other netics, since it has been shown that the kinetic param-hand, report that miagnesium and calcium have no effect on tvary over a pH range of 6.2 to 8.2 (16). All manipu-"dark destruction"; they utilized the cations at concentrations r to phototransformation were carried out at 5 C lower than used in the present studies.…”
Section: W F Thompson (Personal Communication) Noted That Caci2mentioning
confidence: 83%
“…Rye phytochrome samples were purified by the method of Briggs et al (3). Briefly, phytochrome was purified by treatment with 10 Figure 1. CaCd2af-fects the proportion of fast and slow reacting components of phytochrome dark reversion (Table I).…”
Section: W F Thompson (Personal Communication) Noted That Caci2mentioning
confidence: 99%
“…In contrast to the above listed cations, transition metals that form chelate complexes with large stability constants, such as Cd 2., Co 2 § Cu 2 § and Zn 2*, cause spectral denaturation of Pfr (100) and enhance its rate of degradation (57). Treatment of seedlings with EDTA, sulfhydryl compounds, azide, cyanide or carbon monoxide inhibits degradation of Pfr in vivo (9,21).…”
Section: Applicability Of Hypothesis To Phytochromementioning
confidence: 99%
“…In an earlier paper (11), we drew attention to the parallels between some of the observed effects of metal ions on phytochrome-mediated physiological responses and their effects on phytochrome photoreversibility in vitro. At the time, there were a number of possible mechanisms to account for the disappearance of photoreversibility in v'ivo after irradiation.…”
mentioning
confidence: 99%
“…In addition, the relation between phytochrome destruction and metal ions (9,11), sulfhydryl reagents (5), chelating agents (14,17), and plant components such as "'killer factor" (5,6) is poorly understood. These experiments were undertaken to clarify the apparent contradiction between the very low levels of phytochrome found in green tissue and the many phytochrome-mediated responses found in green plants. If phytochrome is produced in meristematic cells, as is indicated by the profiles of phytochrome titer in etiolated plants (2) and the correlation between phytochrome synthesis and cell division in tissue cultures (20), then loss of photoreversibility should occur when the meristematic region becomes and extracts of apical and immediately subapical green tissue of light-grown peas.…”
mentioning
confidence: 99%